Low Solar Power Harvesting With Iot Smart Nodes - R., Hemalatha.; P., Jayabharathi; S., Kalaivani.; R.M, Bommi. (International Journal of Engineering and Technology, 2018)
electronic instruments and many other instruments which mostly depends on power. So the harvesting of power becomes necessary. In order to leave required amount of power to the next generation, we should harvest the power what we have now. In this project we used four modules for harvesting power. Extracting maximum power from a solar power harvester with minimum power transfer loss is the primary goal of this project. The proposed system demonstrates that we can track maximum power point tracking (MPPT) under rapidly changing atmospheric condition. Instead of photovoltaic cell, the solar cells are used for harvesting power. There are totally four modules used and these modules are controlled using a main board. The each power harvesting module consists of wireless transmitters which is controlled by IOT webpage. Also each power harvesting modules consists of wireless transmitter. These transmitters are used to transmit the power to the receiver through wireless networks. All these nodes are controlled using main board. This control board can be user configurable. The smart WSN controlled power harvesting system is also established here.Â Â